EFEKTIFITAS EKSTRAK MANGROVE Rhizophora apiculata (Tomlinson, 1986) DALAM MENGHAMBAT Vibrio parahaemolyticus PENYEBAB PENYAKIT PADA UDANG VANAME Litopenaeus vannamei (Boone, 1931) - Supono Supono; Siti Ning Mulyaningsih; Yeni Elisdiana (Universitas Sriwijaya, 2022)
Vaname (L. vannamei ) shrimp cultivation is currently experiencing problems, one of which is disease caused by Vibrio bacteria, especially V. parahaemolyticus. This type of vibrio is the cause of white feces disease and AHPND in shrimp. Disease control due to Vibrio can be done by utilizing plants that have active compounds as natural antibacterials that are environmentally friendly. Mangrove plants have several active compounds that have great potential as antibacterial. This study aimed to examine some parts of the mangrove plant R. apiculata in inhibiting the activity of V. parahaemolyticus. Three parts of the mangrove plant, namely: roots, stems, and leaves were extracted using methanol. The three extracts were tested for their antibacterial activity against V. parahaemolyticus by several tests such as phytochemical, sensitivity, zone of inhibition, best dose, and toxicity tests. The test results showed that R. apiculata mangrove stem extract had the greatest ability to inhibit V. parahaemolyticus with an effectiveness value of 15.85% with the best dose of 200 mg/L. Toxicity testing using vaname shrimp larvae extract showed that mangrove stems were non-toxic with an LC50 value of 2,155.5 mg/L.Keywords: White feces disease, AHPND, active compounds, extracts, antibacterials